محددات الربحية في شركات التأمين دراسة تطبيقية على شركات التأمين العاملة في سورية - ضاهر حنان; وسوف أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى التعرف على العوامل المؤثرة على ربحية شركات التأمين العاملة في سورية, إسهاماً في مساعدة إدارة تلك الشركات على تهيئة المناخ الملائم بما يضمن لهذه الشركات استمرارها ونجاحها في تحقيق أهدافها وتحقيق التنمية الاقتصادية المنشودة. لتحقيق غرض الدراسة تم جمع البيانات من شركات التأمين العاملة في سورية, وقد استثنيت من الدراسة كلاً من شركة العقيلة للتأمين التكافلي بسبب التزامها بمبادئ الشريعة الإسلامية, والمؤسسة العامة السورية للتأمين لعدم توفر البيانات المالية الخاصة بها. امتدت فترة الدراسة من العام 2009 إلى العام 2013. لغرض تحليل بيانات الدراسة تم استخدام أحد نماذج الـ Panel Data وهو نموذج الانحدار التجميعي. تم تحليل البيانات بالاعتماد على البرنامج الإحصائي7 Eviews. أظهرت نتائج الدراسة أن كلاًّ من الأزمة السياسية والاستثمارات تؤثر إيجاباً على ربحية الشركة, أما الرافعة المالية تؤثر بشكل سلبي على ربحية شركات التأمين, أما حجم الشركة والسيولة لم يظهر لها أثر على ربحية شركات التأمين. This research aims to identify the factors affecting the profitability of insurance companies operating in Syria, a contribution to assist the management of those companies to create the appropriate environment to ensure these companies to sustain and success in achieving their objectives and achieving the desired economic development. To achieve the purpose of the study, data was collected from insurance companies operating in Syria, two companies were excluded from the study, Oqaila Takaful Insurance Company because of its commitment to the principles of Islamic law, and the General Syrian Insurance Corporation because of the lack of of its financial data. The study period spanned from 2009 to 2013. For the purpose of the study data analysis was used a Panel Data model namely the pooled regression. The data were analyzed based on Eviews7. Results of the study showed that both the political crisis and investments positively affect the profitability of the company, while the leverage negatively affect the profitability of insurance companies, the company’s size and liquidity, did not show an effect on the profitability of insurance companies.